Introduction - Paolo Calvetti; Aleksandra Jarosz; Étienne Baudel; Elia Dal Corso; Marc Miyake (Edizioni Ca' Foscari, 2024)
Japan’s ecological variety seems to parallel the multitude of different languages and dialects attested in the Japanese archipelago. In addition to standard Japanese and its dialects, there exist other Japonic languages such as Ryūkyūan and Hachijō, as well as non-Japonic varieties like Ainu. In this volume, four articles explore the importance of a philological approach to sources for historical linguistics: “Adopting a Philological Approach Toward Chishi (地誌)” by Étienne Baudel; “Elements of Sakhalin Ainu Pho- netics, Phonology, and Morphosyntax in Bronisław Piłsudski’s Corpus of Ainu Folk- lore” by Elia Dal Corso; “The Language of Miyako Oral Traditions” by Aleksandra Ja- rosz; “Reflexes of Proto-Ryukyuan Mid Vowels in Haedong Chegukki” by Marc Miyak